# Solve for c 5(4c+1)-3(5c+4)=-c+7(c+7)

5(4c+1)-3(5c+4)=-c+7(c+7)
Simplify 5(4c+1)-3(5c+4).
Simplify each term.
Apply the distributive property.
5(4c)+5⋅1-3(5c+4)=-c+7(c+7)
Multiply 4 by 5.
20c+5⋅1-3(5c+4)=-c+7(c+7)
Multiply 5 by 1.
20c+5-3(5c+4)=-c+7(c+7)
Apply the distributive property.
20c+5-3(5c)-3⋅4=-c+7(c+7)
Multiply 5 by -3.
20c+5-15c-3⋅4=-c+7(c+7)
Multiply -3 by 4.
20c+5-15c-12=-c+7(c+7)
20c+5-15c-12=-c+7(c+7)
Subtract 15c from 20c.
5c+5-12=-c+7(c+7)
Subtract 12 from 5.
5c-7=-c+7(c+7)
5c-7=-c+7(c+7)
5c-7=-c+7(c+7)
Simplify -c+7(c+7).
Simplify each term.
Apply the distributive property.
5c-7=-c+7c+7⋅7
Multiply 7 by 7.
5c-7=-c+7c+49
5c-7=-c+7c+49
5c-7=6c+49
5c-7=6c+49
Move all terms containing c to the left side of the equation.
Subtract 6c from both sides of the equation.
5c-7-6c=49
Subtract 6c from 5c.
-c-7=49
-c-7=49
Move all terms not containing c to the right side of the equation.
Add 7 to both sides of the equation.
-c=49+7
-c=56
-c=56
Multiply each term in -c=56 by -1
Multiply each term in -c=56 by -1.
(-c)⋅-1=56⋅-1
Multiply (-c)⋅-1.
Multiply -1 by -1.
1c=56⋅-1
Multiply c by 1.
c=56⋅-1
c=56⋅-1
Multiply 56 by -1.
c=-56
c=-56
Solve for c 5(4c+1)-3(5c+4)=-c+7(c+7)

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top